Pengaruh Kecanduan Konten Digital terhadap Kualitas Pendidikan Anak; Tantangan dan Solusi di Era Digital - Anugrah Dimas Prayoga; Moh Ilham Maulana Putra; Hasanal Bulkiah Akbar (Kampus Akademik Publiser, 2025)
This research aims to explore the quality of children's education in the digital era, focusing on the influence of technology on the teaching-learning process. The method used is literature study and survey, involving analysis of various scientific publications and data collection through questionnaires. The research findings indicate that technology can enhance access to and quality of education if used effectively, such as expanding the range of learning materials and facilitating more dynamic student-teacher interactions. However, it was also found that the use of technology can pose challenges, such as student distraction due to irrelevant content and unequal access to quality devices and internet connections. The conclusion of this study provides valuable insights into maximizing the benefits of technology in children's education, including management strategies and holistic approaches to addressing emerging challenges. The integration of technology in the educational context must be done carefully and accompanied by appropriate supervision and guidance efforts to optimize the potential of technology in achieving better educational quality.